Myb-Related Fission Yeast cdc5p Is a Component of a 40S snRNP-Containing Complex and Is Essential for Pre-mRNA Splicing - McDonald, W. Hayes (American Society for Microbiology, 1999)
Myb-related cdc5p is required for G(2)/M progression in the yeast Schizosaccharomyces pombe. We report here that all detectable cdc5p is stably associated with a multiprotein 40S complex. Immunoaffinity purification has allowed the identification of 10 cwf (complexed with cdc5p) proteins. Two (cwf6p and cwf10p) are members of the U5 snRNP; one (cwf9p) is a core snRNP protein. cwf8p is the apparent ortholog of the Saccharomyces cerevisiae splicing factor Prp19p. cwf1(+) is allelic to the prp5(+) gene defined by the S. pombe splicing mutant, prp5-1, and there is a strong negative genetic interaction between cdc5-120 and prp5-1. Five cwfs have not been recognized previously as important for either pre-mRNA splicing or cell cycle control. Further characterization of cwf1p, cwf2p, cwf3p, and cwf4p demonstrates that they are encoded by essential genes, cosediment with cdc5p at 40S, and coimmunoprecipitate with cdc5p. We further show that cdc5p associates with the U2, U5, and U6 snRNAs and that cells lacking cdc5(+) function are defective in pre-mRNA splicing. These data raise the possibility that the cdc5p complex is an intermediate in the assembly or disassembly of an active S. pombe spliceosome.